The Zhangjiatun igneous complex in the southeastern margin of the Central Asian Orogenic Belt, NE China: Evidence for an Early Paleozoic intra-oceanic arc. (1st June 2020) - Ma, Hai-Tao; Ma, Xu; Chen, Jia-Fu; Chen, Bin; Li, Chao; Zhou, Li-Min; Yang, Hong-Zhang
Graphical abstract: Highlights: Cambrian to Silurian subduction-related magmatism occurred at the southeastern CAOB. The Zhangjiatun igneous complex was created by intra-oceanic subduction. The Early Paleozoic southeastern CAOB was characterized by double-arc subduction. Abstract: The subduction-accretionary evolution of the southeastern margin of the Central Asian Orogenic Belt (CAOB), consisting of the northern North China Craton, Bainaimiao arc, and Ondor Sum accretionary complex from south to north, is still not well understood. In order to clarify the Early Paleozoic subduction process in the southeastern margin of the CAOB, we conducted geochronological, geochemical, and Sr-Nd-Hf isotope analyses of the Zhangjiatun igneous complex rocks. The Zhangjiatun complex is composed of hornblende gabbro, quartz diorite, and tonalite. Zircon U-Pb dating of the complex yields ages ranging from 486 Ma to 440 Ma. We interpret this result as indicating Early Paleozoic arc magmatism along the southeastern margin of the CAOB. Late Cambrian to Early Ordovician mafic-intermediate intrusions have low-K tholeiitic compositions characterized by low (La/Yb)N (0.4–1.2) and initial 87 Sr/ 86 Sr (0.70439–0.70447) ratios, positive εNd(t) (+6.5 to +7.6), and εHf(t) (+13.5 to +19.0) values. The geochemical values indicate the rocks to be of N-MORB affinities, likely generated by melt differentiation from a depleted mantle. An Early Silurian tonalite exhibits oceanic plagiogranite signatures, expressed by high Na2 O, and low K2 O, Rb, and total REE contents. The tonalite also yields high (La/Yb)N values, low Sr/Y and initial 87 Sr/ 86 Sr (0.70345) ratios, and positive εNd(t) (+3.3) and εHf(t) (+8.0 to +12.5) values. Geochemical modelling suggests that the tonalite may have originated from hydrous melting of hornblende gabbro with a minor contribution from melting of oceanic sediments. The Late Cambrian to Early Ordovician mafic-intermediate intrusions with MORB characteristics likely resulted from initial intra-oceanic subduction along the southern margin of the Paleo-Asian Ocean. We interpret the Early Silurian tonalite to have been generated as the arc became fully developed. We further suggest that the southeastern margin of the CAOB has involved two subduction systems during the Early Paleozoic: a northern south-dipping intra-oceanic arc and a southern north-dipping continental arc.